Colour Blindness Among Male Professional Drivers: A Cross-sectional Study In Karachi - Samira Faiz; Sehrish Zehra; Farhan Qureshi; Seema Mumtaz (Journal of Bahria University Medical and Dental College)
Objective: To determine the frequency of color blindness among male professional drivers of Karachi- Pakistan and the difficulties they experience while driving. Study Design and Setting: A cross-sectional study was conducted aomng 300 male drivers with valid driving licenses operating on local and long routes in Karachi. Methodology: The study was done at various locations in the city of Karachi from September to November 2017. The subjects were tested for vision and color blindness with the help of Snellen’s chart and Ishihara chart respectively. A précised questionnaire was developed keeping in view the study objectives. SPSS version 21.0 was used for data entry and its analysis. Each questionnaire was thoroughly studied and seen for missing data or information before entry. A written informed consent about the study was provided to the subjects in the form of a plain language statement attached to the questionnaire. This study was approved by the ethical review board of Karachi Institute of Medical Sciences (KIMS). Results: Amongst the 300 participants 7 (2.33 %) of the drivers were found to have complete color blindness while 2 (0.66%) were partially colour blind. They preferred day time driving and experience difficulties in recognizing traffic signals and vehicle lights. Conclusion: The frequency of colour blindness was found to be low but it was observed that colour blind drivers face a lot of difficulties while driving. Therefore, easy and practical changes should be made, like shape-coding of signals, and continuous research-based modifications are required to aid these drivers.